Landscape Simplification Constrains Adult Size in a Native Ground-Nesting Bee. - Miles Renauld; Alena Hutchinson; Gregory Loeb; Katja Poveda; Heather Connelly (PLoS ONE)
Bees provide critical pollination services to 87% of angiosperm plants; however, the reliability of these services may become threatened as bee populations decline. Agricultural intensification, resulting in the simplification of environments at the landscape scale, greatly changes the quality and quantity of resources available for female bees to provision their offspring. These changes may alter or constrain the tradeoffs in maternal investment allocation between offspring size, number and sex required to maximize fitness. Here we investigate the relationship between landscape scale agricultural intensification and the size and number of individuals within a wild ground nesting bee species, Andrena nasonii. We show that agricultural intensification at the landscape scale was associated with a reduction in the average size of field collected A. nasonii adults in highly agricultural landscapes but not with the number of individuals collected. Small females carried significantly smaller (40%) pollen loads than large females, which is likely to have consequences for subsequent offspring production and fitness. Thus, landscape simplification is likely to constrain allocation of resources to offspring through a reduction in the overall quantity, quality and distribution of resources.